Prednosti in slabosti avtomobilizma kot temelja turističnega razvoja Slovenije - Uršič, Matjaž (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2022)
The article analyzes the advantages and disadvantages arising from the use of car transport in tourism. Special attention is paid to the analysis of problematic interdependence between tourism and automobile traffic. Presented are factors that potentially obstruct the development of new forms of tourism offer that would be based on a more sustainable use of Slovenia's potentials as a green destination. The article is based on the use of a range of data from official statistics (SURS, Eurostat, Directorate of Infrastructure of the Republic of Slovenia), supplemented by data and findings from other research in the field of transport and tourism. An important part of the article also represents the analysis of value orientations of the population of Slovenia in relation to the perception of the role of tourism and transport.
Keywords: avtomobilizem; avtomobilski promet; Cestni prevoz; Slovenija; trajnostna mobilnost; trajnostni turizem; Turizem; Vrednote (filozofija)